Risk of Aortic Aneurysm and Dissection in Patients with Tuberculosis: A Nationwide Population-Based Cohort Study - Ming-Tsung Chen (MDPI AG, 2021)
Tuberculosis (TB) can cause chronic inflammation. The occurrence of aortic aneurysm (AA) and aortic dissection (AD) may be associated with chronic inflammatory disease, but whether TB increases the risk of AA and AD remains to be determined. This study aimed to investigate the association between TB and the development of AA and AD. We conducted a population-based cohort study using data obtained from the Taiwan National Health Insurance Database. We selected 31,220 individuals with TB and 62,440 individuals without TB by matching the cohorts according to age, sex, and index year at a ratio of 1:2. Cox regression analysis revealed that the TB cohort had a 1.711-fold higher risk of AA and AD than the non-TB cohort after adjustment for sex, age, socioeconomic status, and comorbidities (adjusted hazard ratio = 1.711; 95% confidence interval = 1.098–2.666). Patients with pulmonary, extrapulmonary, and miliary TB had a 1.561-, 1.892-, and 8.334-fold higher risk of AA and AD, respectively. Furthermore, patients with TB at <6 months, 6–12 months, and 1–5 years of follow-up had a 6.896-, 2.671-, and 2.371-fold risk of AA and AD, respectively. Physicians should consider the subsequent development of AA and AD while treating patients with TB.